Comparion methods for determining generators shares in loads, line flows and losses for transmission open access - Mohd Herwan, Sulaiman; Mohd Wazir, Mustafa; Omar, Aliman; Ismail, Daud; Surya, Hardi Amrin; Mohamad Suhaizal, Abu Hassan (Universiti Teknologi Mara (UiTM), 2011)
International Conference on Power Engineering and Optimization Conference (PEOCO 2008), organized by Universiti Teknologi MARA (UITM), 4th - 5th June 2008 at Shah Alam, Selangor.